Self-Assessed Educational Needs of Chinese Pediatric Clinicians Regarding Pediatric Palliative Care: A Cross-Sectional Investigation - Xiaoxia Lu; Yanmei Wang; Jingke Li; Yue-Cune Chang; Niang-Huei Peng (MDPI AG, 2024)
Background: An important first step in enhancing professional palliative care training is to investigate the educational needs of pediatric clinicians in this field. The aims of this research were to analyze the extent of end-of-life care experience of Chinese pediatric clinicians and identify the differing educational needs of physicians and nurses as well as associated impact factors. Methods: A cross-sectional descriptive survey via a structural questionnaire was used in this research. Results: In total, 187 clinicians, comprising 52 physicians and 135 nurses, participated in this study. The topics "pain management", "symptom management", and "discussing the prognosis with family members" were the most expressed educational needs among both physicians and nurses. Compared to nurses, physicians placed greater emphasis on the importance of "communication" and "pain and symptom management" (p < 0.05). Clinicians with more extensive end-of-life care experience more strongly felt the importance of learning about pain management and communication regarding end-of-life care (p < 0.05). Conclusions: Research showed that the education currently provided to pediatric clinicians does not meet their distinctive needs. Future palliative care education must be a continuing multi-level, interdisciplinary program and different education should be provided to physicians and nurses based on their respective needs.